Les chemins de fer au Canada : la troisième ligne transcontinentale - Mackenzie, Kenneth S.; Lowe, Norman; Palmer, Bill (Assurances, 1988)
Most of Canada's railroads were built at the end of the nineteenth century and at the beginning of the twentieth. Construction first began on a small scale at the local level and later expanded to longer fines which led to the creation of the Intercolonial, then the Canadian Pacific and finally other fines which were joined to form our national railways. Following is an article from En voie on the history of the fast transcontinental railway. We thank the authors and the magazine for allowing us to publish this very interesting article.